2019
DOI: 10.3390/s19163602
|View full text |Cite
|
Sign up to set email alerts
|

Bin-Picking for Planar Objects Based on a Deep Learning Network: A Case Study of USB Packs

Abstract: Random bin-picking is a prominent, useful, and challenging industrial robotics application. However, many industrial and real-world objects are planar and have oriented surface points that are not sufficiently compact and discriminative for those methods using geometry information, especially depth discontinuities. This study solves the above-mentioned problems by proposing a novel and robust solution for random bin-picking for planar objects in a cluttered environment. Different from other research that has m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 53 publications
1
12
0
Order By: Relevance
“…The model predictions reached parity with human accuracy levels. This indicated that the quality and consistency of demonstrations became a limiting factor and was a likely reason that our reported accuracy numbers were in line with some results reported for some similar systems [12,51,52] and significantly worse than some others [50]. The differences in applications and the accuracy of the ground truths made a comparison across applications difficult.…”
Section: Discussionsupporting
confidence: 85%
“…The model predictions reached parity with human accuracy levels. This indicated that the quality and consistency of demonstrations became a limiting factor and was a likely reason that our reported accuracy numbers were in line with some results reported for some similar systems [12,51,52] and significantly worse than some others [50]. The differences in applications and the accuracy of the ground truths made a comparison across applications difficult.…”
Section: Discussionsupporting
confidence: 85%
“…The investigated systems were developed for either pickand-place applications [5,12,19,20] or production inspections (i.e., [4] and this work). For planar manipulations [5,12], image-based object recognition would be enough; on the other hand, 3D scanning was utilized for recognizing the objects that were either randomly placed (i.e., [20] and this work) or had arbitrary shapes [19]. The challenges of the robot manipulations increased as the objects Sensors 2020, 20, x FOR PEER REVIEW 9 of 14 mark would be measured during the object following and inline inspection to show the accuracy of the optical inspection.…”
Section: Experiments and Results Of The Proposed Inline Inspectionmentioning
confidence: 99%
“…A comparison between the presented IIIR and some other existing methods that were developed in the past few years is given in Table 3. The investigated systems were developed for either pick-and-place applications [5,12,19,20] or production inspections (i.e., [4] and this work). For planar manipulations [5,12], image-based object recognition would be enough; on the other hand, 3D scanning was utilized for recognizing the objects that were either randomly placed (i.e., [20] and this work) or had arbitrary shapes [19].…”
Section: Experiments and Results Of The Proposed Inline Inspectionmentioning
confidence: 99%
“…The packaging process is divided into two tasks: object-picking and packing. The former means picking one of the items randomly arranged within a container, and it has been tried to be automated in various directions with deep learning including the recent Amazon robotic challenge outcomes [ 1 , 2 , 3 ]. The latter implies placing the picked up item in the most suitable position in another container, and mostly it has been implemented in a theoretical way or in a hybrid form with human collaboration [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%